FUNGSI TARI NTABUH PADA SUKU DAYAK JAWANT DALAM UPACARA PERNIKAHAN DI DUSUN SULANGBETUNG SEKADAU - Anastasia, Indrayani; Ismunandar, Ismunandar; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research was about the function of Ntabuh Dance in a wedding ceremony. This research to analyze the traditional ceremony and to review the function of Ntabuh Dance in a wedding ceremony at Dayak Jawant community in Sulangbetung hamlet. This research used function and cultural theory as the research theory. The method used is descriptive method with qualitative research form and anthropological approach. The source of data in this research was Fransiskus as a dancer Ntabuh Dance. The data of this research was the ritual function of Ntabuh Dance in the wedding ceremony. The writer used observation, interview, and documentation study as the techniques of data collection. The technique of research data analysis were analyzed and interpreted the function of Ntabuh Dance in a wedding ceremony. The result of this research showed that the function of Ntabuh Dance was one of the rituals that existed in the wedding ceremony of Dayak Jawant. Ntabuh dance was a ritual dance that aimed to fill customs in the wedding ceremony to rid themselves of customs payable. The results of this study were expected to be implemented in the VIII class artistic arts lessons in junior high school in the second semester. Keywords: function, Ntabuh dance, Dayak Jawant, wedding ceremony